COSTS OF HOME-BASED TELEMEDICINE PROGRAMS: A SYSTEMATIC REVIEW. (30th July 2018) - Michaud, Tzeyu L.; Zhou, Junmin; McCarthy, Molly A.; Siahpush, Mohammad; Su, Dejun
Abstract : Objectives: The aim of this study was to systematically investigate existing literature on the costs of home-based telemedicine programs, and to further summarize how the costs of these telemedicine programs vary by equipment and services provided. Methods: We undertook a systematic review of related literature by searching electronic bibliographic databases and identifying studies published from January 1, 2000, to November 30, 2017. The search was restricted to studies published in English, results from adult patients, and evaluation of home telemedicine programs implemented in the United States. Summarized telemedicine costs per unit of outcome measures were reported. Results: Twelve studies were eligible for our review. The overall annual cost of providing home-based telemedicine varied substantially depending on specific chronic conditions, ranging from USD1, 352 for heart failure to USD206, 718 for congestive heart failure (CHF), chronic obstructive pulmonary disease (COPD), and diabetes as a whole. The estimated cost per-patient-visit ranged from USD24 for cancer to USD39 for CHF, COPD, or chronic wound care. Conclusions: The costs of home-based telemedicine programs varied substantially by program components, disease type, equipment used, and services provided. All the selected studies indicated that home telemedicine programs reduced care costs, although detailed cost data were either incomplete or not presented in detail. A comprehensive analysis of the cost of home-based telemedicine programs and their determinants is still required before the cost efficiency of these programs can be better understood, which becomes crucial for these programs to be more widely adopted and reimbursed.